Pelatihan Pembuatan Website Berbasis CMS di SMK Ciracas - Muliyati, Dewi (MJI Publisher by PT Mitra Jurnal Indonesia, 2022)
Abstract In order to bridge the gap between current industry demands and vocational school curricula, university academics directly teaching Content Management System (CMS) training at vocational schools has proven to be successful. These efforts ensure that students receive comprehensive and state-of-the-art training in web development as well as management. Implementing CMS training in vocational schools gives students the golden opportunity to acquire and refine the technical skills that are so much needed in today’s digital age. The integration of CMS training into vocational school curricula forms a solid foundation for students to pursue careers in a variety of fields such as web design, digital marketing, and content management, empowering them to excel in the digital era. The results of this training show that the training participants, namely students, have successfully developed a website and mastered the use of various tools on the WordPress platform. The resulting output covers a wide range of types of websites, confirming the success of the training in equipping students with practical skills that can be applied in a variety of industry contexts. This success encourages students to seize broad and relevant career opportunities amidst rapid technological developments and market needs. Abstrak Pelatihan Content Management System (CMS) yang diberikan secara langsung oleh akademisi universitas di sekolah kejuruan membuktikan menjadi jembatan efektif dalam mengatasi kesenjangan antara tuntutan industri terkini dan kurikulum sekolah kejuruan. Upaya ini memastikan bahwa siswa mendapatkan pelatihan yang komprehensif dan mutakhir dalam pengembangan serta manajemen web. Implementasi pelatihan CMS di sekolah kejuruan memberikan siswa peluang emas untuk memperoleh dan mengasah keterampilan teknis yang sangat dibutuhkan di era digital saat ini. Integrasi pelatihan CMS di dalam kurikulum sekolah kejuruan membentuk dasar yang kokoh bagi siswa untuk mengejar karir di berbagai bidang seperti desain web, pemasaran digital, dan manajemen konten, memberdayakan mereka untuk mencapai keunggulan di era digital. Hasil dari pelatihan ini menunjukkan bahwa peserta pelatihan, yaitu siswa, berhasil mengembangkan website dan menguasai penggunaan berbagai alat dalam platform WordPress. Output yang dihasilkan meliputi beragam jenis website, menegaskan keberhasilan pelatihan dalam membekali siswa dengan keterampilan praktis yang dapat diterapkan dalam berbagai konteks industri. Keberhasilan ini mendorong para siswa untuk meraih peluang karir yang luas dan relevan di tengah pesatnya perkembangan teknologi dan kebutuhan pasar.